Administration of Research Programme in Nigerian Public Universities: Problems and Way Forward - Ogunode Niyi Jacob; Jegede Deborah; Adah Samuel; Audu Elizabeth I; Ajape Temitope Solomon (Universitas Syiah Kuala, 2020)
Research programme is one of the major programme of the universities. It is a key to the university’s development. Research programme of the universities is one of the key indicators used to measure the performance of the universities. The administration of research programme in Nigerian public universities faces many problems. Therefore, this article discusses the problems facing the administration of research programme in public universities in Nigeria. The article identified; inadequate research funding, unstable academic calendar/strike Actions, inadequate infrastructural facilities, brain-drain, insecurity, corruption, poor technological advancement/poor ICT literacy. Others are poor participation of private sector in research development and lack of conducive working (research) environment as problems facing the administration of research programme. To address these problems, this article recommends adequate funding of research, provision of adequate infrastructural facilities, ensure stable academic staff, fight all institutions in the universities, ensure adequate security in the universities, encourage private participation in the development of research, provision of conducive research environment and Soften of the conditions attached to research Grants.ethod.